2014
DOI: 10.1016/j.cgh.2013.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Remission: The Ultimate Therapeutic Goal in Ulcerative Colitis?

Abstract: Ulcerative colitis (UC) is a disease of the mucosal layer, and activity of the disease is assumed to be related to mucosal appearance. Mucosal healing has emerged as a major therapeutic goal in UC. Whether mucosal healing should be the ultimate therapeutic goal in these patients is unknown. Even when endoscopy suggests mucosal healing, evidence of histologic activity has been observed. Histologic healing requires complete recovery of the colonic mucosa, with absence of inflammation or structural changes. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 36 publications
4
139
0
2
Order By: Relevance
“…The final sample included 256 patients (113 women [44.1%] INTRODUCTION Anti-tumor necrosis factor (anti -TNF) antibodies improve the quality of life in patients with inflammatory bowel disease (IBD) 1 and likely modify the course of the disease via mucosal healing and a reduced rate of surgeries. [2][3][4][5][6][7] With an acceptable adverse event profile, TNF inhibitors can be considered the safest and most effective therapy for IBD. 8 The earlier in the course of the disease the anti -TNF treatment is introduced, the higher the probability of response and long -term remission.…”
Section: Results Demographic Characteristics Of Patients Receiving Anmentioning
confidence: 99%
“…The final sample included 256 patients (113 women [44.1%] INTRODUCTION Anti-tumor necrosis factor (anti -TNF) antibodies improve the quality of life in patients with inflammatory bowel disease (IBD) 1 and likely modify the course of the disease via mucosal healing and a reduced rate of surgeries. [2][3][4][5][6][7] With an acceptable adverse event profile, TNF inhibitors can be considered the safest and most effective therapy for IBD. 8 The earlier in the course of the disease the anti -TNF treatment is introduced, the higher the probability of response and long -term remission.…”
Section: Results Demographic Characteristics Of Patients Receiving Anmentioning
confidence: 99%
“…In UC, varying data on achieving MH with the use of 5-ASA (36,9%-80%) [31,32], azathioprine (53%) [33] and biologics 32%-62% [34][35][36][37] exist, depending on the used definition of MH and duration of follow up. In the case of CD similar results for budesonide (24%) [38], azathioprine (16.5-73%) [38][39][40], combinations of azathioprine and biologics (43,.4%) [39,40], and biologics (20%-63%) [39][40][41][42] exist.…”
Section: Discussionmentioning
confidence: 51%
“…Newly defined treatment targets, such as deep or histological remission come from endpoints defined for clinical IBD trials [40,[43][44], but are not widely accepted or integrated in the IBD guidelines [25][26][27][28]. Surprisingly, almost half of all respondents used deep remission as a key treatment target in daily clinical practice, which suggests that practice is being shaped prior to development or revision of guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence indicates that persistent histological disease is associated with an increased risk of hospitalization, colectomy, relapse, and colorectal neoplasia [19][20][21]. Thus, some authors have suggested that histological healing may be the ultimate therapeutic goal especially in UC [22].…”
Section: Histological Mucosal Healingmentioning
confidence: 99%